The Production of Tannin Acyl Hydrolase from Aspergillus niger - YUNITA ARIAN SANI ANWAR; . HASIM; I MADE ARTIKA (Indonesian Society for microbiology, 2007)
The aim of this research was to produce tannin acylhydrolase (tannase) from Aspergillus niger isolated from cacao pod. The first step of the study included determination of optimal pH, temperature, and incubation period to produce tannase. Optimal conditions obtained for tannase production were pH 5.5, a temperature of 28 oC and an incubation period of 3 days. Optimization of production medium was conducted. The media tested were solid and liquid wheat flour media with a concentration of tannic acid as inducer at 0, 3, 5, and 7% (wt/vol). The best production medium was solid medium with tannic acid concentration of 5% (wt/vol).